On class and earnings trajectories: The use of class and earnings to study intergenerational mobility. (December 2020) - Yaish, Meir; Kraus, Vered
Abstract: Sociologists and economists differ in how they study intergenerational social mobility. For sociologists, intergenerational mobility is examined between economic standings, such as class, which are multidimensional, and derived from an individual's position in the labor market. Economists, instead, have a unidimensional view on this issue, and thus focus on income as the measure between which social mobility is examined. This paper contributes to this literature by examining the association between class and life course earnings trajectories. Utilizing a unique intergenerational data-set supplemented by life course earnings information on Israeli men and women, we show that class, as measured in mid-career, is associated with distinct life course earnings trajectories. We discuss the implications of this finding, and conclude that in the absence of life course earning data, class can serve as a proxy for earnings trajectories.